Passively scanned, single‐fiber optical coherence tomography probes for gastrointestinal devices. Issue 7 (16th June 2022) - Otuya, David O.; Dechene, Nicholas M.; Poshtupaka, Darina; Judson, Seth; Carlson, Camella J.; Zemlok, Sarah K.; Sevieri, Evan; Choy, Peter; Shore, Rachel E.; De León‐Peralta, Esmarline; Cirio, Alissa A.; Rihm, Tyler W.; et al.
Abstract: Background/Objectives: Optical coherence tomography (OCT) uses low coherence interferometry to obtain depth‐resolved tissue reflectivity profiles (M‐mode) and transverse beam scanning to create images of two‐dimensional tissue morphology (B‐mode). Endoscopic OCT imaging probes typically employ proximal or distal mechanical beam scanning mechanisms that increase cost, complexity, and size. Here, we demonstrate in the gastrointestinal (GI) tracts of unsedated human patients, that a passive, single‐fiber probe can be used to guide device placement, conduct device−tissue physical contact sensing, and obtain two‐dimensional OCT images via M‐to‐B‐mode conversion. Materials and Methods: We designed and developed ultrasmall, manually scannable, side‐ and forward‐viewing single fiber‐optic probes that can capture M‐mode OCT data. Side‐viewing M‐mode OCT probes were incorporated into brush biopsy devices designed to harvest the microbiome and forward‐viewing M‐mode OCT probes were integrated into devices that measure intestinal potential difference (IPD). The M‐mode OCT probe‐coupled devices were utilized in the GI tract in six unsedated patients in vivo . M‐mode data were converted into B‐mode images using an M‐to‐B‐mode conversion algorithm. The effectiveness of physical contact sensing by the M‐mode OCT probes was assessed by comparing the variances of the IPD values when the probe was in physical contact with the tissue versus when it was not. The capacity of forward‐ and side‐viewing M‐mode OCT probes to produce high‐quality B‐mode images was compared by computing the percentages of the M‐to‐B‐mode images that showed close contact between the probe and the luminal surface. Passively scanned M‐to‐B‐mode images were qualitatively compared to B‐mode images obtained by mechanical scanning OCT tethered capsule endomicroscopy (TCE) imaging devices. Results: The incorporation of M‐mode OCT probes in these nonendoscopic GI devices safely and effectively enabled M‐mode OCT imaging, facilitating real‐time device placement guidance and contact sensing in vivo. Results showed that M‐mode OCT contact sensing improved the variance of IPD measurements threefold and side‐viewing probes increased M‐to‐B‐mode image visibility by 10%. Images of the esophagus, stomach, and duodenum generated by the passively scanned probes and M‐to‐B‐mode conversion were qualitatively superior to B‐mode images obtained by mechanically scanning OCT TCE devices. Conclusion: These results show that passive, single optical fiber OCT probes can be effectively utilized for nonendoscopic device placement guidance, device contact sensing, and two‐dimensional morphologic imaging in the human GI tract in vivo. Due to their small size, lower cost, and reduced complexity, these M‐mode OCT probes may provide an easier avenue for the incorporation of OCT functionality into endoscopic/nonendoscopic devices.